Formação da corona de lisozima e albumina em nanopartículas de ouro via modelagem molecular - Melo, Rafael Leandro Fernandes (Universidade Federal Rural do Semi-Árido, 2019)
Gold nanoparticles (AuNPs) are part of a biocompatible nanometric universe in which their mechanical, electrical, magnetic and optical properties make them interesting for biological applications. These efficiently convert light into heat, a property that makes them highly important for biological and therapeutic sensations. Interest in the interactions between AuNPs and proteins has been growing steadily in the scientific community. Its high biocompatibility causes them to create interactions with biological molecules contained in the blood plasma, forming a crown on its surface called the corona effect, when this effect has a predominance of proteins, it is called corona protein (PC). The unpredictable effects related to CP affect critically the therapeutic responses, in which the AuNPs have as purpose. In this work, we performed an investigation using classical molecular modeling of the corona effect in gold nanoparticles (PC @ AuNP) using two proteins most common in blood plasma, human lysozyme (lyzozyme, LYZ, PDB 2nwd) and human albumin English, human serum albumin, HSA, PDB 4k2c), with four spherical AuNPs of 2,4,6 and 8 nm in diameter. The AuNPs had their energies and geometries optimized, and the proteins had their energies and light atoms optimized, all via classical modeling using the Universal force field. After optimizations, the AuNPs were placed to interact with each protein separately, performing scans in order to obtain the potentials of interaction energies. The results show the relationship between the energy potential of interaction with the distance between the centroids of the AuNPs with the proteins. The highest potential energies are visualized and indicate the preferred regions of interaction of the proteins with each AuNP. The results of the interactions of lysozyme with AuNPs (LYS @ AuNPs), suggest that the increase of AuNPs size is proportional to the energy potential, and in addition these have three preferential stabilization regions. The results obtained between albumin and AuNPs (HSA @ AuNPs) do not present a direct proportion between the increase of AuNPs with increased energy potential, but also presented three preferential regions of interaction
Keywords: Efeito corona; Nanopartículas de ouro; Modelagem molecular; Corona effect; Gold nanoparticles; Molecular modeling; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA